2015
DOI: 10.1007/s00345-014-1470-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimated functional renal parenchymal volume predicts the split renal function following renal surgery

Abstract: The postoperative FRV and renal function could be predicted preoperatively using a 3-D image reconstructive system, preoperative routine diagnostic imaging, and preoperative sCr level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…To overcome the limitation of serum creatinine-based renal function evaluation, several studies have reported the usefulness of CT-based renal parenchymal volumetry. 18,19,25 According to these reports, there was a significant correlation between mean percent RPV loss and the mean percent eGFR loss (r = 0.52-0.79). However, although several reports have compared CT-based volumetry with nuclear renal scan in living kidney donors, there is no such report for nephron-sparing surgery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To overcome the limitation of serum creatinine-based renal function evaluation, several studies have reported the usefulness of CT-based renal parenchymal volumetry. 18,19,25 According to these reports, there was a significant correlation between mean percent RPV loss and the mean percent eGFR loss (r = 0.52-0.79). However, although several reports have compared CT-based volumetry with nuclear renal scan in living kidney donors, there is no such report for nephron-sparing surgery.…”
Section: Discussionmentioning
confidence: 97%
“…To overcome the limitation of serum creatinine‐based renal function evaluation, several studies have reported the usefulness of CT‐based renal parenchymal volumetry . According to these reports, there was a significant correlation between mean percent RPV loss and the mean percent eGFR loss ( r = 0.52–0.79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many 3-D simulation software packages enable researchers to estimate renal preservation by a detailed surgical process with computational methods [20,21]. In this study, sophisticated film technology, Synapse Vincent, was used for the soft volumetric analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al addressed the clinical impact of split renal volume (SRV) calculated on the basis of the findings of computed tomography (CT) used to evaluate renal function in patients with renal cell cancer who underwent partial nephrectomy. 1 Previous studies have shown the correlation between renal parenchymal volume determined by CT-based renal volumetry and loss of estimated glomerular filtration rate, [2][3][4] and other studies of living kidney donors have compared the findings of CT-based renal volumetry and those of nuclear renal scans. [5][6][7] On the basis of the results of these studies, the present study shows the possible usefulness of CT-based volumetry along with nuclear renal scans for estimating split renal functions after nephron-sparing surgery.…”
mentioning
confidence: 99%